Konsep Diagnosis dan Penatalaksanaan Fraktur Osteoporosis Terkini - Aryana, I Gusti Ngurah Wien; Febyan, Febyan (Jurnal Penyakit Dalam Indonesia, 2023)
Osteoporosis is a metabolic bone disease that is caused by a decreased amount of bone mass, and microarchitectural damage to bone tissue that affects the bone to break easily. Osteoporosis can be divided into primary and secondary etiologies. Vertebral, hip, distal radius, and proximal humerus are the most common predilection of fracture complication due to osteoporosis. The diagnosis of osteoporotic fractures is established based on the identification of risk factors, general clinical manifestations, specific manifestation from each fracture predilection, and advanced examinations, including radiology imaging and dual-energy x-ray absorptiometry. The purpose of osteoporotic fractures management in elderly is a stable fixation with early mobilization that will induce an optimal activation of osteoblast for new bone formation.